Verifying the Correctness of UML Statechart Outpatient Clinic Based on Common Modeling Language and SMV - Abdul Samat, Pathiah; Azwarrudin, Muhammad Amsyar; Mohd Ali, Norhayati; Admodisastro, Novia (International Journal of Integrated Engineering, 2021)
Unified-modelling language (UML) is a standard general purpose modelling language, which is widely, used in system design of banking, biological, plantation and healthcare. Recently, there are many systems of healthcare are modeled using behavioral diagram such as UML statechart for design purposes. However, the behavior of healthcare statechart is rarely verified to ensure it is behaving as we needed. In software engineering, a software should be verified before it is transform to the further phases. In this paper, a statechart of outpatient clinic is verified to ensuring the correctness of its design. Therefore, to achieve our objective, we have applied Common Modeling Language (CML) and SMV model checker for verification formal system modeling and specification of property of statechart outpatient clinic. The result shows that the statechart of outpatient clinic is behave as required and the statechart is allowable to transform to the next phase.